A review of the development of electronic portfolios in education and health care disciplines: supporting students' learning and continuing professional development - Ng, Curtise; White, P.; McKay, Janice (Australian Institute of Radiography, 2007)
Using a portfolio approach is not a new idea in health care disciplines as an alternative assessment format and for continuing professional development (CPD). Increasingly, the use of electronic portfolios is noted in the literature. This paper critically reviews developments, features, advantages and problems relating to different modes of operation. The review is conducted with educational and CPD usage in mind particularly for the health care professions where reflective practice, applied learning and outcomes-based education are prominent pedagogies. The most appropriate types of electronic portfolio practice are also discussed. Although a number of problems were noted with earlier types of electronic portfolio, they have been rectified by the current existing modes of operation. It is suggested that the development of reflective abilities and professional development are well served with the currently available technology incorporating capabilities of collaborative learning, storage and management, portability and access, flexibility and multimedia contents. Although web and web database portfolios tend to be role models for electronic portfolios, the most appropriate type depends on the values of the stakeholders. This paper concludes that web portfolios provide greater flexibility in building and are feasible in small size situations such as subject-based portfolio practice or personal use for CPD records. Web database portfolios should be the only choice at institution or professional society level because of the capability to serve a large population. Reflective learning and professional development can be captured using electronic portfolio systems, and further advances on the current technology will evolve. What is important in establishing an electronic portfolio is to ensure that the content requirements remain the most important aspect and that development is seen to support this aspect rather than focusing on the technical process of portfolio building.